Teatro negro e identidade: as metamorfoses do (a) artista negro (a) no teatro e na dramaturgia brasileira - Silva, Daniel Ribeiro da (2021)
Given the relevance that the theme of affirming black racial identity represents, the result of a tireless militancy of the Brazilian black movement, this work started from critical social psychology and the theory of Antonio da Costa Ciampa, who states that identity is metamorphosis in search of emancipation, to discuss the theme of the possibility of existing processes of identity metamorphosis with an emancipatory meaning, experienced by black people in contemporary times. We considered that although there are identity policies formulated by the hegemonic racial group, which tend to describe in a derogatory way who they are and how black people should be treated, on the other hand, throughout the history of the black presence on Brazilian soil, there has been a questioning of that place of subordination and a claim for recognition in the public sphere. The research focused on one of these contemporary experiences of seeking recognition in the public sphere: the theater movement known as Teatro Negro (Black Theater). As our focus of analysis, we geographically delimited the black theatrical manifestation that takes place in the city of São Paulo and greater São Paulo in contemporary times, and identifying in this movement a space of affirmation of the collective black identity, our aim, as a general objective of the dissertation, is to investigate what are the possibilities of strengthen the affirmation of a collective black identity in Brazilian society, in order to effect changes in the forms of recognition offered to this racial group in the public sphere; besides, as a specific objective, we analyze how occurs, to the individual, the process of constitution of an affirmative black racial identity, in a country that seeks to disseminate an ideology that sustains the nonexistence of forms of racism in the nation . The relevance of the research is manifested in the need to evaluate the emancipatory potential present in the anti-hegemonic identity politics, vindication of recognition in the public sphere; since it is possible that, at times, such movements have a regulatory character only. Moreover, the indicator used to show whether an antihegemonic identity politics has allowed the occurrence of metamorphoses emancipating the lives of individuals, it is the presence of qualitative autonomy gains and the possibility of developing a political identity, as stated by Ciampa. The data collection method used was the narrative of life history and future project, in addition to bibliographic research. The use of a single participant in the research took into account the premise defended in qualitative studies on identity as a metamorphosis that, according to Ciampa, the singular materializes the universal. The analysis of the narrative of life history and future project brought by the research participant provided the identification of the existence of possibilities for the occurrence of metamorphoses with an emancipatory meaning in contemporaneity